Estudo computacional da não conservação do spin: reação do ferro porfirina com diferentes ligantes axiais e reação de haber-weiss em fase gasosa - Leitão, Ezequiel Fragoso Vieira (2017)
In this thesis work was carried out a computational study of some reactions forbidden and allowed by spin. The first reaction involves investigated the dissociation of the ligands iron porphyrins ((FeP(L)2, onde, L = H2O, dimethylnitrosamine, Imidazole and Pyridine) and the other concerns the Haber-Weiss mechanism to species such as R-OOH + O2–, onde R = H, CH3 e CH3CH2. The mechanisms of the both reactions represent a major challenge from the point of view of computational choice of the appropriate method since it involves a large number of stationary points and, in some cases, with different spin multiplicities. For dissociation reactions with Fe-porphyrins were chosen ligands weak and strong field ligands. At this stage we used various DFT methods (OLYP, BP86, oTPSS, M06, M06L, M06L2X, B3PW91, PBE1PBE, B2PLYP e DSD-PBEP86) to estimate the order of spin states for the metal in the form Fe(III) and Fe(II) and some procedures to calculate and potential energy surface of these reactions. The results show that the function of the double-hybrid class DSD-PBEP86 can correctly predict the order of the spin states of the systems studied metalloporphyrin and characterize the crossing of the surfaces of the different spin states during the reaction. The second study the Haber-Weiss reaction with three kinds of peroxides, namely hydrogen peroxide, peroxide and methyl ethyl peroxide. For this problem, we were mapped some mechanisms of reactions that lead to the formation of the products reported in the literature. The reaction of H2O2 with O2– occurs by two competing reaction channels. The major product (O2 + O-H2O) follows by a reaction forbidden by spin, while the minor product (H2OO3–) assumes a reaction allowed by spin. The reaction spin forbidden undergoes intersystem crossing region and the mechanism proves to be governed by the change of the overall electronic configuration during the reaction. In reaction CH3OOH + O2–, for the first time, is proposed a reaction mechanism and a prediction about the enthalpy of the different reactions that may occur. In the case of the reaction between the methyl, the ethyl peroxide and superoxide is allowed by spin. The computational results of the reaction enthalpy of these reactions are in good agreement with the values found in the literature.